Aesthetic, creative and innovative uses for photosensitive glass in art-glass production: case studies in studio practice - May, Heather (Curtin University, 2010)
This research is situated in a space between the broad fields of art-glass design, art, science and the technology of alternative photographic printing processes. It is an experimental project with a core research question. ‘Can photosensitive glass be made more accessible to artists working in art-glass, design or art practice’?The focus of this research is located in the almost forgotten niche of ‘photosensitive’ glass. ‘Photo-sensitive and photo-chromic glasses contain ultraviolet light-sensitive metals, gold, silver or copper. The selective development of color can be controlled by placing a mask or photographic film in contact with the glass. When exposed to ultraviolet radiation, then heated, the glass changes from clear to opal, reproducing the pattern on the glass. The image developed is permanent and will not fade as would a similar image in photo-chromic glass.’ (Kohler 1998, 23-24). Glass: An Artist’s Medium. Section 2. Properties of Glass. Iola, WI54990-001. USA: Krause Publications.Through systematic experimentation, the methods indicating how photosensitive glass can be incorporated into selected traditional glass-making techniques have been identified. Traditional glass making techniques include: o Pulling of molten glass from a glass furnace to make stringers, canes, rods, murrine and/or mosaics a hot glass technique. o Crushing and recycling, making chunk de verre and pate de verre, a warm glass technique. o Bead-making, button-making and core-forming, all hot glass techniques. o Kiln work in the form of kiln casting/slumping and simple open-face Pate de Verre, a warm glass technique. o The casting of molten glass from the glass furnace into sand for sandcasting and the forcing of hot molten glass into moulds are hot glass techniques. o Free-blowing and mould blowing, hot glass techniques. o Acid etching and acid embossing, particularly hazardous cold glass techniques are only discussed not attempted.These selected techniques are presented as case studies that have been analysed and the experiments documented to identify methods and processes that demonstrate the potential of photosensitive glass as an art medium. The details of successful experimentation are fully documented according to a laboratory processes, formulae and colour analysis. This extensive research material will hopefully enable designers and glass artists to extend their creative practices and when using the outcomes to develop hybrid and innovative processes in a wide range of contemporary studio based and commercial applications. The research outcomes of this enquiry into the use of photosensitive glass in creative glass processes represent an extensive and original contribution to knowledge that I hope will be shared by studio artists and commercial glass professionals in art and design.